New species and new records of Palaearctic Meessiidae and Tineidae (Lepidoptera: Tineoidea) - R. Gaedike (SHILAP, 2021)
Newly described and illustrated in the family Meessiidae are Eudarcia topoliacola Gaedike, sp. n., and Novotinea cretica Gaedike, sp. n., and in the family Tineidae: Hapsifera tadjikistana Gaedike, sp. n., Nemapogon paracyprica Gaedike, sp. n., Neurothaumasia hackeri Gaedike, sp. n., Neurothaumasia kaschmirella Gaedike, sp. n., Dinica nepalica Gaedike sp. n., Elatobia rufarea Gaedike sp. n., Tinea caucasicola Gaedike, sp. n., Proterospastis meyi Gaedike, sp. n. An illustration of the imago of Myrmecozela mongolica Petersen, 1965 is presented. First records for countries are established for ten species.